2006
DOI: 10.4049/jimmunol.176.6.3593
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Underlying FOXP3 Induction in Human T Cells

Abstract: FOXP3 is playing an essential role for T regulatory cells and is involved in the molecular mechanisms controlling immune tolerance. Although the biological relevance of this transcription factor is well documented, the pathways responsible for its induction are still unclear. The current study reveals structure and function of the human FOXP3 promoter, revealing essential molecular mechanisms of its induction. The FOXP3 promoter was defined by RACE, cloned, and functionally analyzed using reporter-gene constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
342
8
12

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(384 citation statements)
references
References 55 publications
22
342
8
12
Order By: Relevance
“…It is also important to note that our results do not dispute the crucial role of TCR in human Treg cell commitment. Analysis of the FOXP3 promoter area has identified several TCR-responsive sites (26) and TCR ligation can lead to up-regulation of FOXP3 (27), although this is not necessarily accompanied by suppressive function (28 -30). In all likelihood the posited Treg cell maturation pathway involves TCR-dependent checkpoints, perhaps selecting for autoreactive clones among a stochastically generated FOXP3 ϩ precursor pool (3-7).…”
Section: Resultsmentioning
confidence: 99%
“…It is also important to note that our results do not dispute the crucial role of TCR in human Treg cell commitment. Analysis of the FOXP3 promoter area has identified several TCR-responsive sites (26) and TCR ligation can lead to up-regulation of FOXP3 (27), although this is not necessarily accompanied by suppressive function (28 -30). In all likelihood the posited Treg cell maturation pathway involves TCR-dependent checkpoints, perhaps selecting for autoreactive clones among a stochastically generated FOXP3 ϩ precursor pool (3-7).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, several studies have reported that FOXP3 mRNA is expressed by in vitro human activated non-regulatory T cells [14,[20][21][22], which may gain regulatory activity [20,22]. Recent studies on the FOXP3 promoter identify a non-repressive chromatin structure that together with a specific transcriptional regulation programme may explain the ability of activation to induce FOXP3 expression in CD4 + CD25 -T cells [23]. Gavin and colleagues [24] have recently reported that activation-induced FOXP3 expression in human T cells, as measured by flow cytometry, is transient and insufficient to induce Treg, proposing that sustained high level FOXP3 expression is required for Treg phenotype and function.…”
Section: Foxp3 Induction By Activationmentioning
confidence: 98%
“…11,28 CsA can inhibit this thymic generation of CD4 þ FoxP3 þ T REG by impairment of TCR signaling, and more specifically by reducing the NFATdependent FoxP3 promotor activity. 29 Rapamycin inhibits biochemical pathways required for the cell cycle progression from the G1 to S phase, but allows the initial signal transduction upon TCR triggering. 15 We found that rapamycin does not affect the thymic CD4 þ FoxP3 þ T-cell generation.…”
Section: Discussionmentioning
confidence: 99%